2011
DOI: 10.3844/ajessp.2011.26.34
|View full text |Cite
|
Sign up to set email alerts
|

Physical Composition, Nutrients and Contaminants of Typical Waste Dumping Sites

Abstract: Problem statement: The composition of wastes is quite variable depending upon the generating source and mode of collection. Most of the material from the domestic activities will be organic in nature and contains essential plant nutrients, whereas the dumping material of commercial and industrial wastes usually contains appreciable amounts of heavy and potentially toxic metals and organic pollutants. Approach: Objective of the present study was to characterize the physico-chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Este possui elevada carga de poluentes orgânicos e inorgânicos, os quais, ao entrar em contato com o solo, podem modificar suas características físicas, químicas e biológicas, bem como as das águas subterrâneas (MEUSER et al, 2011 Os solos possuem grande capacidade de retenção dos elementos metálicos, porém, se esta capacidade for ultrapassada, os metais alterarão sua disponibilidade para o meio ambiente, tornando-se facilmente lixiviáveis, com consequente aporte em águas subterrâneas (OLIVEIRA et al, 2010). Um aspecto fundamental na determinação das concentrações dos elementos traços nos solos refere-se a sua movimentação no perfil, o que não depende apenas das características do íon metálico, mas também das propriedades físicas e químicas de cada tipo de solo (FONTES et al, 2000).…”
Section: Introductionunclassified
“…Este possui elevada carga de poluentes orgânicos e inorgânicos, os quais, ao entrar em contato com o solo, podem modificar suas características físicas, químicas e biológicas, bem como as das águas subterrâneas (MEUSER et al, 2011 Os solos possuem grande capacidade de retenção dos elementos metálicos, porém, se esta capacidade for ultrapassada, os metais alterarão sua disponibilidade para o meio ambiente, tornando-se facilmente lixiviáveis, com consequente aporte em águas subterrâneas (OLIVEIRA et al, 2010). Um aspecto fundamental na determinação das concentrações dos elementos traços nos solos refere-se a sua movimentação no perfil, o que não depende apenas das características do íon metálico, mas também das propriedades físicas e químicas de cada tipo de solo (FONTES et al, 2000).…”
Section: Introductionunclassified
“…Meuser et al (2011) found the nitrogen content of waste dumping site to range between 0.34 and 0.54%. However, higher levels of potassium and phosphorus were observed due to the high solubility of K and P in solid wastes that get readily leached to soil.…”
Section: Chemical Analysis Of the Soil Samplementioning
confidence: 99%